2018
DOI: 10.2320/matertrans.md201705
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nano-Ag Fabricated by the Electrical Spark Discharge Method for Restraining Aspergillus Niger

Abstract: The traditional nano preparation method is costly and time-consuming, and contains hazardous chemical constituents, thus affecting the characteristics and applications of nanocolloid. The Electrical Spark Discharge Method (ESDM) used in this paper prepares Nano-Ag colloid in deionized water, which is characterized by low cost, continuous and rapid production, and is free of chemical substances. According to the UV-Vis analysis of Nano-Ag, it has a peak at about 392 nm. Based on Zetasizer analysis, the minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…When the temperature is higher than 440 °C, a CuINC has a sodium chloride structure (a-CuI) [3]. Currently, two methods exist for preparing a nanocolloid (NC): the chemical method [4,5] and physical method [6][7][8]. One chemical method of producing an NC is mixing soluble copper salt with potassium iodide or sodium iodide solution [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…When the temperature is higher than 440 °C, a CuINC has a sodium chloride structure (a-CuI) [3]. Currently, two methods exist for preparing a nanocolloid (NC): the chemical method [4,5] and physical method [6][7][8]. One chemical method of producing an NC is mixing soluble copper salt with potassium iodide or sodium iodide solution [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of the basic researches has important meanings for the industrial application, since the inkjet process is a simple and low-cost fabrication method. Second paper describes synthesis of hybrid nanomaterial of Fe 3 O 4 / polyaniline, whose properties were carefully examined, and its ability of removing arsenic in wastewater was studied by Trung et al 191) In the third one, fabrication of Ag nanoparticles by the electrical spark discharge method and its application for restraining aspergillus Niger was investigated by Tseng et al 192) Fourth paper reported an investigation of nanosized Ag particles using graphene quantum dots by Hoang et al 193) Synthesis of ZnTiO 3 and Ag/ZnTiO 3 was reported in the fifth paper by Anh et al, 194) in which their antibacterial performance was also studied. The sixth paper by Nguyen et al showed photoactivity of reducing graphene oxide and titanium dioxide composite for cinnamic acid degradation.…”
mentioning
confidence: 99%